Energy-efficient HVAC system through chillers' capacity sizing for a library building. Issue 2 (26th January 2017) - Wang, F. J.; Lin, H. W.; Tu, W. D.; Shiau, C. H.; Hung, Y. C.
ABSTRACT: Heating, ventilating, and air-conditioning (HVAC) systems in commercial buildings consume the largest amount of energy. Recent surge in energy cost necessitates constant re-evaluation of HVAC system for most of the buildings. The objective of this study is to present the strategic approach on energy saving analysis of the HVAC system and chiller sizing optimization for a library building. Energy modeling code (eQUEST) for buildings simulation has been applied to verify and predict the long-term energy consumption of HVAC systems. To improve the accuracy of simulation results, the actual performance curves of the chillers and pumps were the inputs of curve fitting data from on-site field measurements data. Energy consumption data acquisition from the building energy management system (BEMS) for one year has been conducted comprehensively to calibrate energy modeling and to quantify energy saving results. The results revealed good agreement between energy modeling and BEMS data with the error of less than 10%. Besides, energy savings through the chillers' sizing based on cooling load profile could be achieved satisfactorily by utilizing energy modeling by using the actual chiller performance curve. The energy saving for HVAC system can be obtained satisfactorily at the saving of 110, 362 kWh per year. It is expected that the study will stimulate a more robust investigation of energy-efficient and cost-effective HVAC system specific for library buildings.